Service-Learning for Youth Leadership The Case of Hong Kong - T. L. Shek, Daniel; Ngai, Grace; C. F. Chan, Stephen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This edited book looks at Service-Learning - a valuable means to promote civic engagement and youth leadership in students through the application of student learning to needy people in the community. It describes selected Service-Learning projects in different areas by highlighting the subjects being offered, service site(s), service projects completed, evaluation findings and reflections of teachers. Although Service-Learning has grown tremendously in the West, its development in different Chinese societies is still at its infancy. Thus, this book provides valuable insights on the implementation and future directions of the Service-Learning movement in different Chinese societies by documenting related experiences and sharing successful stories. It also examines related evaluation findings and impacts on students to show that through Service-Learning, empathy, social awareness, social responsibility and psychosocial skills of students can be strengthened and can eventually promotetheir quality of life. In addition, the book highlights that Service-Learning activities promote the well-being of clients and communities being served. It also stimulates thinking and sharpens the thoughts of educators, administrators and those who wish to promote the quality of life of students and service recipients through Service-Learning.
Chapter 1. The new education reform in Hong Kong: Emergence of the 4-year undergraduate program -- Chapter 2. Service-Learning as a vehicle for youth leadership: The case of The Hong Kong Polytechnic University -- Chapter 3. Case 1: Promotion of the development of migrant children in Hangzhou and Shanghai -- Chapter 4. Case 2: Promotion of the development of underprivileged children in Hong Kong -- Chapter 5. Case 3: Service Leadership through serving socially deprived students: Experience gained from corporate-community partnership (Project WeCan) -- Chapter 6. Case 4: Serving clients in a drug rehabilitation agency as a vehicle to promote service leadership in university students -- Chapter 7. Case 5: Supporting STEM education through Service-Learning -- Chapter 8. Case 6: Reaching out across the digital divide: integrating engineering and non-engineering students in engineering projects to serve children in Cambodia -- Chapter 9. Case 7: Building Assistive Technology Solutions with computer knowledge (CS1) -- Chapter 10. Case 8: Helping parents through modernizing ancient Chinese wisdom -- Chapter 11. Case 9: Expressive wearable art as therapy for the vulnerable groups -- Chapter 12. Case 10: Promoting quality of life through fashion for function and design -- Chapter 13. Case 11: Promotion of social development through tourism -- Chapter 14. Case 12: Nutrition and lifestyle consulting for communities in developing regions -- Chapter 15. Case 13: Designing a better environment through analyzing the built environment -- Chapter 16. Case 14: Development of a pioneer e-learning package on Service-Learning -- Chapter 17. Engaging teachers in teaching Service-Learning subjects: Strategies and challenges -- Chapter 18. Impact of Service-Learning on university students: Quantitative findings -- Chapter 19. Impact of Service-Learning on university students: Qualitative findings -- Chapter 20. The Service-Learning movement in Hong Kong: Challenges ahead.
Keywords: Quality of life; Developmental psychology; Youth -- Social life and customs; Quality of Life Research; Developmental Psychology; Youth Culture